2021
DOI: 10.1007/s00226-021-01349-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mould resistance of wood with cinnamaldehyde chitosan emulsion

Abstract: Mould fungi can grow on virtually any substrate and are particularly common on cellulosic materials such as wood. Fungicides can limit the risk of mould attack, but increasing concerns about pesticide use have encouraged a search for more natural protection methods. Cinnamaldehyde is a promising antifungal candidate, but has not been fully effective. In this study, chitosan and cinnamaldehyde were used to prepare an emulsion to reduce the volatility of cinnamaldehyde, and the antimould performance of the emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Bi et al [ 102 ] prepared modified solvents with chitosan and cinnamaldehyde as raw materials. After treating wood with the modified solvents, they studied the inhibitory effect of cinnamaldehyde chitosan modified solvent on the growth of Aspergillus niger on the wood surface.…”
Section: Improvement Of Antibacterial Properties Of the Wood Surfacementioning
confidence: 99%
“…Bi et al [ 102 ] prepared modified solvents with chitosan and cinnamaldehyde as raw materials. After treating wood with the modified solvents, they studied the inhibitory effect of cinnamaldehyde chitosan modified solvent on the growth of Aspergillus niger on the wood surface.…”
Section: Improvement Of Antibacterial Properties Of the Wood Surfacementioning
confidence: 99%
“…Furthermore, the fluorescence intensity dimmed compared with the sound wood as well. It can be inferred that T. versicolor depolymerized the lignin along with the colonization of the hyphae and spread in the cell lumina [58]. After exposed to brown rot fungi, the fluorescence intensity of wood samples weakened and the cell walls became thinner at 16 weeks, implying lignin can be modified at the advanced stages [56].…”
Section: Mycelial Distribution and Conversion Of Constituentsmentioning
confidence: 99%
“…The weight loss of wood treated with solution of caffeine and chitosan after the leaching procedure was about 10%, which suggests that application of chitosan limited leaching of caffeine from the wood structure, but it did not completely retain caffeine in the wood. According to the literature data, wood was impregnated with a mixture of chitosan and various bioactive compounds or substances, including propolis, silver nanoparticles, cinnamaldehyde, (3-(2-aminoethylamino)propyl) trimethoxysilane or as a chitosan-copper complex with organic fungicides (tebuconazole and propiconazole), and showed resistance against decay wood fungi (C. puteana, T. versicolor and G. trabeum) and molds (A. niger, P. citrinum and T. viride) (Sun et al 2012;Silva-Castro et al 2018;Casado-Sanz et al 2019;Bi et al 2021;Fang et al 2021). The results of the preliminary research indicated that addition of chitosan from crab shells to caffeine solution resulted in a reduction in the caffeine concentration needed to inhibit the mold (A. niger, P. funiculosum, P. variotti and T. viride) growth (Kwaśniewska-Sip et al 2019b).…”
Section: Decay Resistance Of Treated Woodmentioning
confidence: 99%
“…The molecular size of chitosan and its concentration also impact the anti-mold properties of chitosan-treated wood (Gorgij et al 2014;El-Gamal et al 2016;Oldertrøen et al 2017). Chitosan was also applied to wood treatment in combination with other substances, including cinnamaldehyde, polyethylene glycol, propolis extract and silver nanoparticles (Silva-Castro et al 2018;Casado-Sanz et al 2019;Bi et al 2021;Fang et al 2021).…”
Section: Introductionmentioning
confidence: 99%